Addition of selenium nanoscale to high diets with wheat bran and its effect on Biochemical and characteristics blood and somatic cell count in milk in Awassi ewes (NTU Journal of Agriculture and Veterinary Science, 2025)
The study was conducted to investigate the effect of selenium nanoscale in improving the utilization of high wheat bran diet using 15 Awassi ewes weighing 51.58 ± 1.71 kg and their ages ranged between 3-4 years, the ewes were divided into three groups, each group included five ewes, the ewes were fed during the study period, which amounted to 72 days, and the amount of feed provided to ewes was equivalent to 1.5 kg of dry matter per ewe per day. The first group (control) was fed a diet high in barley grains with an ideal percentage of wheat bran, in the second group the ewes were fed a diet that contained less barley with a bran percentage raised to 35% of the components of the diet, while the third group was fed a diet similar to the second diet with daily doses of ewes with 0.3 mg / ewe of nano-selenium. The results indicated that there were no significant differences (P?0.05) for the biochemical blood traits, in Blood standards for a blood picture, there was no significant difference in the number of white blood cells, the percentage of lymphocytes, the mean corpuscular volume, the number of red blood cells, and blood hemoglobin. At the same time, the ratio of granulocytes increased for each of the second and third treatments, the platelet Counts decreased for each of the second and third treatments, and the number of somatic cells was much less in the second period of the study in Bran and selenium groups compared to control.